Effects of electric fields on the release and content of extracellular vesicles - Yihua Wang; Gregory A. Worrell; Hai‐Long Wang (Journal of Extracellular Biology)
Abstract Extracellular vesicles (EVs) are small membrane‐bound structures that originate from various cell types and carry molecular cargos to influence the behaviour of recipient cells. The use of EVs as biomarkers for diagnosis and as delivery vehicles for treatment in a wide range of human disease is a rapidly growing field in research and clinical practice. We hypothesized that electric fields (EFs) could influence the release and content of EVs. To examine this hypothesis, we developed a specialized bioreactor enabling cells to thrive in a three‐dimensional setting, replicating in‐vivo conditions amidst programmable EF environments. We established a three‐step EV purification protocol to achieve high‐density production of EVs. We also performed mass spectrometry‐based proteomics analysis on EV‐carrying proteins and used high‐resolution nanoparticle flowcytometry for single‐vesicle analysis. Findings from this report suggest that electrical stimulation, employing physiologically relevant amplitudes typical in therapeutic deep brain stimulation, influences the release of EVs and their cargo content in a frequency‐dependent fashion. This conclusion could carry significant implications for both fundamental biological understanding and medical advancements. First, it raises an intriguing question about how the endogenous electrical activity of neuronal and other cellular assemblies influence the production and composition of EVs. Second, it reveals a novel underlying mechanism of how therapeutic electrical stimulations can modulate EVs and treat human brain disorders. Third, it provides a novel approach to utilize electrical stimulation for generating desired EV cargos in a programmable setting.